1995
DOI: 10.1177/00220345950740011101
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Human High-molecular-weight Salivary Mucins (MG1) to Hemophilus parainfluenzae

Abstract: In human saliva, two different mucin populations can be distinguished, viz., high-molecular-weight mucins (MG1, mol. wt > 1 x 10(6)) and low-molecular-weight mucins (MG2, mol. wt approximately 125 kD). The carbohydrate moiety of MG1 displays a wide spectrum of oligosaccharide structures, varying in composition, length, branching, and acidity. The biological significance of the heterogeneity in carbohydrate structures of mucins is unclear. The present investigation focused on the question whether MG1, because o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 22 publications
1
23
0
1
Order By: Relevance
“…In order to confirm this finding additional experiments with isolated protein are needed. Most oral bacteria, however, do not bind MUC5B (35,75), and likewise we did not find an association between MUC5B concentrations and the ex vivo adherence of S. sanguis and S. gordonii, or C. albicans coadherence with S. gordonii. The association between adherence of S. mitis and cystatin S concentrations represented the only negative correlation, suggesting an inhibitory effect of cystatin S.…”
Section: Microbial Adherence and Coadherence During Acute Stresssupporting
confidence: 55%
“…In order to confirm this finding additional experiments with isolated protein are needed. Most oral bacteria, however, do not bind MUC5B (35,75), and likewise we did not find an association between MUC5B concentrations and the ex vivo adherence of S. sanguis and S. gordonii, or C. albicans coadherence with S. gordonii. The association between adherence of S. mitis and cystatin S concentrations represented the only negative correlation, suggesting an inhibitory effect of cystatin S.…”
Section: Microbial Adherence and Coadherence During Acute Stresssupporting
confidence: 55%
“…We can conclude that the latter is most likely because S. mutans attachment and biofilm formation in the presence of MUC5B are significantly decreased at most time points compared to the levels in the presence of methylcellulose. There are at least three potential mechanisms by which MUC5B could protect the surface from bacterial colonization: (i) MUC5B could bind or agglutinate bacteria, which would allow planktonic bacteria to be swept out of the oral cavity with salivary flow but enhance bacterial attachment to surfaces coated with MUC5B (14,25,(37)(38)(39)(40)(41)(42)(43)(44), (ii) MUC5B could have the opposite effect, where its heterogeneous glycan chains repel bacteria, thereby preventing surface attachment (9,11,(45)(46)(47), or (iii) MUC5B could directly downregulate S. mutans genes involved in attachment and biofilm formation. In our case, it appears that MUC5B is repelling S. mutans and/or directly influencing genetic modifications that protect the glass and hydroxyapatite surfaces from bacterial attachment and biofilm formation.…”
Section: Sucrose Enhances S Mutans Attachment and Biofilm Formationmentioning
confidence: 99%
“…Defects in mucin production can lead to diseases such as ulcerative colitis when mucins are underproduced or cystic fibrosis and asthma when mucins are overproduced (4)(5)(6). In addition, studies have shown that mucins can interact with microbes, such as Helicobacter pylori, Haemophilus parainfluenzae, and human immunodeficiency virus (7)(8)(9)(10). These diseases and microbial interactions highlight the necessity of mucins as one of the body's key natural defenses; however, few studies have focused specifically on the connection between MUC5B salivary mucins and oral diseases.…”
mentioning
confidence: 99%
“…Moreover, several pathogenic bacteria other than H. pylori bind to MUC5B and/or sulfo-Le a , and our results may therefore be extrapolated to these microorganisms. Examples are Escherichia coli (90), Staphylococcus aureus (91), Candida albicans (92), Bordetella pertussis (93), Hemophilus influenzae (94), and Fusobacterium nucleatum (Groenink J, Veerman ECI, Nieuw Amerongen AV. 1999, unpublished data).…”
Section: J a Bosch Et Almentioning
confidence: 99%